2003
DOI: 10.1039/b210185h
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of halide-mediated hydrogen-bonding and alkyl substitution in the construction of two-dimensional rhombic (4,4) grids using bis(N-alkylamidino-O-alkylurea)copper(ii) halides

Abstract: A series of hydrogen-bonded networks based on bis(N-alkylamidino-O-alkylurea)copper(II) cations, [CuL 2 ] 21 , bridged by either chloride or bromide have been synthesised, of which six have been structurally characterised by single crystal X-ray diffraction methods. The [CuL 2 ] 21 cation acts as a four-connecting centre and forms 2-D rhombic (4,4) grids for the majority of the compounds studied. However, the grids do not adopt a common intermolecular hydrogen-bonding pattern. Three distinct systems can be dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…1), through the hydrogen bonded supramolecular synthon -OH … F-B-F … HO-. 3,15 The two oxygen atoms O1 and O2 are pushed quite close together (3.642(3) A ˚) by the anion, and the alternating molecules A and B are held in a zig-zag orientation with a geometry that anticipates a pro-tetrahedral imprinting in the crystal architecture: the long axes of molecules A and B within a chain form angles of 109.5u (C1(i)-C1-C19-C19(i)). (ii) The most relevant class of contacts shorter than the sum of van der Waals radii regards CH … F interactions formed by all the hydrogen atoms ortho to the pyridinic nitrogen in both complexes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…1), through the hydrogen bonded supramolecular synthon -OH … F-B-F … HO-. 3,15 The two oxygen atoms O1 and O2 are pushed quite close together (3.642(3) A ˚) by the anion, and the alternating molecules A and B are held in a zig-zag orientation with a geometry that anticipates a pro-tetrahedral imprinting in the crystal architecture: the long axes of molecules A and B within a chain form angles of 109.5u (C1(i)-C1-C19-C19(i)). (ii) The most relevant class of contacts shorter than the sum of van der Waals radii regards CH … F interactions formed by all the hydrogen atoms ortho to the pyridinic nitrogen in both complexes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In 2003, the copper(II) chloride complex consisting of two L 2 ligands, [Cu(L 2 ) 2 ]Cl 2 , has been structurally studied and reported [22] that the copper(II) center are coordinated by two symmetry-related N,N-bidentate L 2 ligands in a trans configuration to give a square planar geometry. In the present work, compounds 1 and 2 contain only a single molecule of L 1 and L 2 ligands, respectively, which only differ in the N-substitution sidearm groups, NH 2 for 1 and NH 2 CH 2 Ph for 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…27 Their binding ability to nucleobases has been previously investigated and found that they are indeed capable of binding to the N3 cytosine by the replacement of the chloride ligands. 28 In addition, the related monomeric copper(II) complexes [Cu(L 1 ) 2 Cl 2 ] and [Cu(L 2 ) 2 Cl 2 ] with a square-planar geometry 29 have also been reported to exhibit potential DNA-interacting properties and antimicrobial activities against Campylobacter. 30 To continue our research, the complexes 1 and 2 have been intensively studied in terms of the DNA interacting and biological properties.…”
Section: Introductionmentioning
confidence: 99%